Quality indicators for clinical care of patients with hypertension: scoping review protocol. Issue 7 (16th July 2019) - Djasri, Hanevi; Laras, Sekar; Utarini, Adi
Abstract : Introduction: Cardiovascular diseases impose significant financial impact on countries implementing universal health coverage (UHC). Hypertension is a primary disease that will lead to more severe conditions without adequate clinical care. The quality of its clinical care must be well assessed in order to measure the effective coverage of people with hypertension in UHC. This study aims to identify indicators that can be used to measure the quality of clinical care provided to patients with hypertension in healthcare facilities. Methods and analysis: This review will be conducted using the six stages of the scoping review method: identifying the research question, searching for relevant studies, selecting studies, charting the data, collating, summarising and reporting the results, and conducting consultation exercises. The review will include all quality indicators used for clinical care of patients with hypertension at any healthcare facility. All research designs will be included. Search strategies are developed using the medical subject headings and keywords related to hypertension and quality indicators. Several electronic databases, that is, MEDLINE, Cochrane, Scopus and Web of Science, including clinical-guideline databases from Agency for Healthcare Research and Quality, National Institute for Health and Care Excellence, National Health Service Evidence and Medical Information Network Distribution Service, and also grey literature will be used. Two researchers will screen the titles and abstracts and review the full text of selected articles to determine the final inclusion. The results will be summarised quantitatively, using numerical counts, and qualitatively, using thematic analysis. The data extraction will include a complete list and detailed profile of all indicators. Stakeholder consultation will be conducted at the beginning and after preliminary results to translate findings to the potential knowledge users. Ethical considerations and dissemination: Reviews of published articles are considered secondary analysis and do not need ethical approval. The findings will be disseminated through various strategies, such as policy briefs, conferences, peer-reviewed journals, and on selected websites relevant to the subject. Study status: Data collection for the scoping review will include publications up to May 2019, and the analysis will start in June 2019.